Empagliflozin inhibits increased Na influx in HFpEF cardiomyocytes and reduces arrhythmic activity in human atrial trabeculae. (3rd October 2022) - Trum, M; Schollmeier, E; Riechel, J; Lebek, S; Reuthner, K; Keller, K; Wester, M; Provaznik, Z; Schmid, C; Maier, L; Arzt, M; Wagner, S
Abstract: Background: Heart failure with preserved ejection fraction (HFpEF) is a major health problem associated with substantial morbidity and mortality. However, the underlying pathophysiological mechanisms are poorly understood, and effective treatment strategies are scarce. Importantly, SGLT2i, which have been suggested to improve cellular Na and Ca homeostasis in HFrEF, have recently been shown to also improve clinical outcomes in patients with HFpEF. Interestingly, post-hoc analyses of clinical data suggest an involvement of anti-arrhythmic effects of SGLT2i. Purpose: We tested, if isolated human atrial cardiomyocytes from patients with HFpEF exhibit an increased Na influx that is responsive to treatment with the SGLT2i empagliflozin (Empa) and if Empa has anti-arrhythmic properties in human atrial trabeculae. Methods: Atrial biopsies were obtained from 101 patients undergoing elective cardiac surgery. Na influx was measured as increase in [Na]i during Na/K-ATPase inhibition in isolated cardiomyocytes loaded with the Na-sensitive fluorescence dye Asante Natrium Green–2 AM (ANG-2). Western Blot and HDAC4 pulldown assay were used to investigate NaV1.5 expression/phosphorylation as well as CaMKII expression/autophosphorylation and activity. Anti-arrhythmic effects of Empa were evaluated as the reduction in premature atrial complexes (PACs), which were induced in electrically field-stimulated (1Hz) human atrial trabeculae by superfusion with isoproterenol (100 nM) and high Ca (3.5 mM). Results: Compared to patients without heart failure (NF), Na influx was almost doubled in HFpEF patients (NF vs HFpEF: 0.21±0.02 vs 0.38±0.04 mmol/L/min (N=7 vs 18); p=0.005) (Fig. 1D, E). CaMKII expression, CaMKII autophosphorylation, CaMKII activity, and CaMKII-dependent NaV1.5 phosphorylation were significantly increased in atrial biopsies of HFpEF patients, whereas NaV1.5 protein abundance remained unchanged (Fig. 1A–C). Consistent with these results, the increased Na influx was significantly reduced by treatment with the specific CaMKII inhibitor autocamtide-2 related inhibitory peptide (AIP) and the late INa inhibitor tetrodotoxin (TTX) (Fig. 1D, E). Importantly, Empa also abolished the increased Na influx in HFpEF cardiomyocytes (Fig. 1D, E). Multivariate linear regression analysis, adjusting for clinical co-variates, revealed HFpEF to be an independent predictor of cardiomyocyte Na handling. In line with Empa-mediated inhibition of Na influx, the frequency of PACs in human atrial trabeculae was significantly reduced by Empa (Fig. 1F, G). Conclusion: This is the first study to demonstrate increased Na influx in human cardiomyocytes from HFpEF patients potentially by an increased CaMKII-dependent NaV1.5 phosphorylation. Excitingly, treatment with Empa decreases this Na influx in HFpEF cardiomyocytes and reduces isoproterenol-induced arrhythmic activity in human atrial trabeculae, which could contribute to the cardioprotective effects of this drug in patients with HFpEF. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Else Kröner-Fresenius-Stiftung, Deutsche Forschungsgemeinschaft